Value relevance of available-for-sale financial instruments (AFS) and revaluation surplus of PPE (REV) components of other comprehensive income - Yousefi Nejad, Maryam; Ahmad, Azlina (2017)
Value relevance studies have thus far provided mixed evidence.Studies also found that fair value reporting has a significant impact on the value relevance of other comprehensive income. Additionally, most studies on value relevance of other comprehensive income focused on developed countries where the capital market is more efficient.In these settings due to the existence of active market, fair valuation of assets may not pose a major problem.In Malaysia the mandatory reporting of comprehensive income by all listed firms based on the requirement of FRS101, coincides with the adoption of FRS139 the standard for financial instrument and could be an interesting setting to investigate.This study hypothesized that other comprehensive income and its components are associated with share price.The results indicate that other comprehensive income and its components are value relevant.The results indicate that the move towards a more comprehensive income reporting through the preparation of the Statement of Comprehensive Income results in more informative financial reporting.